Mind the Gap-Is Economic Growth in India Leaving Some States Behind? - Purfield, Catriona (IMF Working Papers; Working Paper ;, 2006)
This paper examines how growth has varied across India's states. It finds that (i) the income gap between rich and poor states has widened; (ii) rich and faster-growing states have been more effective in reducing poverty; (iii) poor and slower-growing states have had little success in generating private sector jobs; (iv) labor and capital flows do little to close income gaps; and (v) the volatility in economic growth is greatest in poor states. Differences in states' policies affect the cross-state pattern of growth. Greater private sector investment, smaller governments, and better institutions are found to have a positive impact on growth.